Utilizing moving-mass actuated stabilizers for pitch and roll control in hydrofoil-based autonomous surface vehicles: A direct CFD analysis integrated with auto-control algorithm - Shang, Yuchen; Horrillo, Juan; Jose, Alwin (Ocean engineering, 2025)
An innovative control system utilizing a moving mass actuated stabilizer is proposed to address inherent stability challenges for an in-house developed hydrofoil-based autonomous surface vehicle (HASV), where the Proportional-Derivative (PD) algorithm is applied to regulate the pitch and roll stability. In order to precisely and practically investigate and optimize the PD controllability of the system, an Unsteady Reynolds-Averaged Navier-Stokes (URANS) CFD-based control investigation approach is introduced, where the dynamic moving mass process is integrated into the CFD scheme using customized user-defined functions. This approach combines the detailed analysis capabilities of CFD with the precision of PD control. Verification and validation of the CFD simulations against recirculating water tunnel scaled model tests were conducted. Subsequently, CFD-based control simulations were performed to study the effects of the P and D coefficients on the HASV's pitch and roll controller, leading to the selection of suitable PD coefficients. Further studies analyzed roll and pitch motion control under different initial incline angles and wave conditions. The controllability of the proposed moving mass actuated stabilizer is tested through the CFD-based control investigation approach, ensuring the proposed control system's performance can be precisely investigated under diverse operational scenarios. •A novel concept utilizing a moving mass to regulate the pitch and roll motion of the HASV was proposed.•The hydrodynamic performance of the scaled HASV's substructure was tested in a recirculating water tunnel.•The moving mass PID controller is integrated into the CFD scheme to optimize the control system.•HASV's roll and pitch control capabilities were verified through direct CFD-PD simulations.